Organic Solvents for Determination of Bacterial Endotoxin Index in Water-Insoluble Pharmaceutical Substances - O. V. Shapovalova; G. V. Dolgova; N. P. Neugodova; G. A. Sapozhnikova (Антибиотики и Химиотерапия)
Substances for manufacture of parenteral drugs require control by the «Bacterial Endotoxin» (BE) Index with the LAL-test. The aim of the study was to show possible applicability of organic solvents in BE determination by the gel-thromb test in case of water-insoluble pharmaceutical substances. The results confirmed that ethyl alcohol practically had no effect on the endotoxin activity. In the routine assays it is advisable to test solutions of the substances at the alcohol concentration of 6% below.